Analysis of the demographic bonus influence on Gross Regional Domestic Product (GRDP) - Aisyah Ameilia; Cut Aliyyah; Riky Aulia Rachman Marpaung; Uci Aulia Sinaga; Nasrullah Hidayat (International Journal of Applied Finance and Business Studies, 2023)
This study aims to determine the influence of demographic bonus on GRDP in North Sumatra Province. Secondary data sourced from Central Bureau of Statistics (BPS) regarding the Demographic Bonus consisting of HDI, Dependency Ratio, Labor Force Participation Rate, and GRDP were used. The data included a panel of 33 districts/cities in North Sumatra for three years from 2020 to 2022. The analytical approach used in this study was Fixed Effect regression analysis. The findings reveal that HDI has a statistically significant and positive influence on GDP in North Sumatra. In contrast, the Dependency Ratio shows a statistically insignificant and negative impact on GRDP, while TPAK shows a statistically insignificant and positive impact on GRDP in North Sumatra.